(untitled) (BIRDEM Medical Journal, 2012)
Objectives: This study was conducted to assess the relationship of Fasting Plasma Glucose and Plasma Glucose 2 hours after 75 gram glucose load with HbA1c in subjects who were not detected before as diabetic, pre diabetic or non diabetic. Methods: Total eight hundred and seventy eight subjects of both sexes coming to do for an Oral Glucose Tolerance Test (OGTT) were included in the study. Fasting and plasma glucose 2 hours after 75 gram glucose load were measured by hexokinase method. HbA1c was measured by high performance liquid chromatography (HPLC) method. Results: According to OGTT among the total study subjects 48.7%(n=428) had DM, 17.1% (n=150) had Pre DM and 34.2% (n=300) were non diabetic. Correlation coefficient between Fasting Plasma Glucose and HbA1c was 0.551 (p.000) and correlation coefficient between HbA1c and plasma glucose at 2 hours after oral glucose load was 0.475 (p.000). Conclusion: This study showed moderate degree of relationship between Fasting Plasma Glucose and HbA1c and between HbA1c and plasma glucose 2 hours after 75 gram glucose load in population never diagnosed before as diabetic, pre diabetic or non diabetic. DOI: http://dx.doi.org/10.3329/birdem.v2i2.12307 Birdem Med J 2012; 2(2) 81-83